2015
DOI: 10.1093/cid/civ120
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Infectious Disease Consultation on Quality of Care, Mortality, and Length of Stay in Staphylococcus aureus Bacteremia: Results From a Large Multicenter Cohort Study

Abstract: ID consultation is associated with better adherence to quality measures, reduced in-hospital mortality, and earlier discharge in patients with SAB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
164
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 236 publications
(187 citation statements)
references
References 39 publications
11
164
3
Order By: Relevance
“…In two previous observational studies outside of Asia, the adherence rates of follow‐up blood culture were better than in our study (31%3 and 61%2). These adherence rates were improved by interventions, including infectious diseases service consultation (41%3 and 80%2), and this improvement was associated with better survival 2, 3. Furthermore, observational studies have reported that infectious disease service consultation was independently associated with reduced SAB‐related mortality 3, 11.…”
Section: Discussioncontrasting
confidence: 84%
See 3 more Smart Citations
“…In two previous observational studies outside of Asia, the adherence rates of follow‐up blood culture were better than in our study (31%3 and 61%2). These adherence rates were improved by interventions, including infectious diseases service consultation (41%3 and 80%2), and this improvement was associated with better survival 2, 3. Furthermore, observational studies have reported that infectious disease service consultation was independently associated with reduced SAB‐related mortality 3, 11.…”
Section: Discussioncontrasting
confidence: 84%
“…Previous observational studies have reported a similar mortality rate for SAB (15–40%) as in our study 2, 3, 4, 5, 6, 9, 10. However, the sources of bacteremia differed significantly between studies.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Early surrogate measures of "success" could then be validated against these 'true' outcomes. Given that increased mortality following sepsis can be demonstrated for up to 2 years post event [29] It is also important that studies comparing treatment for BSI ensure that other evidence-based approaches known to influence clinical outcomes (such as seeking and addressing a removal source of infection or ID consultation for S. aureus BSI [30]), are applied consistently between arms and compliance recorded.…”
Section: Bsi Is a Common Condition Encountered By Id Physicians And Cmentioning
confidence: 99%